Understanding the urban space: The relationship between free space and urban voids in Erechim-RS - Alves, Luciana Sobis; Bueno, Ayrton Portilho (National Journal of City Management, 2020)
This article presents a study based on the urban structure of the city of Erechim-RS. Furthermore, it seeks to understand the relations between the public form of the city and its free spaces, making it possible to verify if those spaces are characterized as urban voids. Concerning the objectives of the work, the methodology is based on a morphological analysis with survey and mapping of data in addition to the development of the syntactic analysis of the urban network by the Spatial Syntax Theory method to superimpose this information and understand the current city conformation. The research is justified by the fact that public open spaces in the city are not configured as a planned system and the fact that some appear to be underused. It exposes the essential concepts for the development of work such as urban morphology and spatial syntax, public empty spaces, and their appropriation, contemporary city and urban voids. The study points out that public open spaces are mainly located in some neighborhoods in the central area, which is an area with greater integration, and a considerable part of the neighborhoods are unassisted from such spaces. Due to the current situation, some of these spaces are characterized as urban voids.